PEMBUATAN BUKU REFERENSI SUPERHERO INDONESIA SEBAGAI UPAYA MENGENALKAN PRODUK BUDAYA LOKAL - Setiawan, Ryan; Bahruddin, Muhammad; Dewanto, Thomas Hanandry (Jurnal ArtNouveau, 2014)
The term superhero are familiar by Indonesian people. This is due to the rise of media that contains things related to superhero like movies, comics, animated series, toys, etc. Indonesia has its own original superhero that was popular in the 1960s-1980s. However, in the middle of many superheroes are popping up overseas, Indonesian superhero rarely notable even not known by the Indonesian people themselves. one way to introduce Indonesian superhero is through books. In addition, rarely found there wasnt even a book that discusses indonesias superhero with modern visuals. The purpose of this book is to introduce Indonesian superheroes as one of the local cultural products to the people of indonesia that indonesia ought to be proud of. This study uses qualitative methods, through the interview process, focus group discussion, and observations. After the data is obtained, then the results of the analysis it can be concluded that many of the superheroes have a positive impact and should be known. the superhero himself had a positive impact, such as educating, bringing moral messages, and increase imagination. from the results of the analysis, then obtained a keyword that is âepicâ, which means the story of heroism and extraordinary. so the concept of the book is âepicâ, with a powerful theme. supporting media books were also made such as leaflets and websites. this book is expected to Indonesian Superhero to be reintroduced in indonesia that was once popular Â in his time.